PENANGANAN ANAK KORBAN KEKERASAN DALAM RUMAH TANGGA DI WILAYAH HUKUM KEPOLISIAN RESOR LABUHANBATU - Citra Yani Barus; Reny Widyastuti; Jaminuddin Marbun (JURNAL PROINTEGRITA, 2019)
The purpose of this study was to find out and understand the handling of child victims of family violence in the Labuhan Batu Resort Police, the role of Special Service Rooms in providing protection for victims of domestic violence, obstacles faced by Special Service Room officers in dealing with victims of domestic violence.The results of the study show that handling child victims of family violence in the Labuhan Batu Resort Police is manifested in various fields of life, among others in the field of law, so that legal certainty must be upheld by children's rights can be realized. The RPK (Special Service Room) of Labuhan Batu Regional Police is part of the National Police born to handle cases of domestic violence. RPK has a role in providing protection to victims 'witnesses in providing protection to victims' witnesses in cases of domestic violence.